Parents' Attitudes toward Immunization and its Relation with Pediatric Immunization Compliance at Primary Health Care Centers in Karbala City, Iraq - Hussain, Eitidal; Mohammed, Zahid (Iraqi National Journal of Nursing Specialties, 2021)
Objective(s): To assess parents' attitude toward immunization and its relation with their compliance and to find out the relationship between parents' attitude and their socio-demographic characteristics.Methodology: A descriptive design is conducted from the period of 19th September 2020 to the 6th of March 2021. A non-probability (convenient) sample of (292) parents was selected from (5) primary health care centers in Karbala city. These centers are distributed throughout (2) primary health care sectors selected randomly as (20%) from each sectors. The questionnaire is developed and composed of three parts: First part: parent's socio-demographic characteristics, Second part: parents' attitude domain, which involves (13 items), and Third part: child's immunization status and reason for non-compliancy by parents with the routine immunization schedule. The reliability of the questionnaire is determined through a pilot study and the content validity through a panel of (17) experts. The data are collected by the questionnaire. The data are analyzed through using the Statistical Package of Social Sciences (SPSS version 22.0) which is performed through the use of descriptive and inferential statistical analysis procedures.Results: The results of the study indicate that most of the study sample have high (good) attitude toward children immunization and are significantly associated with their residence. Also, the child's is partially immunized for more than 60% of the children of the study sample (parents). In addition, the study results reveal that there is no significant association between parents' attitudes towards immunization and their compliance to the routine immunization schedule for their children. Recommendations: The study recommends that it is necessary to raise parents awareness of the importance of immunization by implementing educational programs, activating the role of traditional and social media, and promote periodically assessment to cover child's immunization timings.